2017
DOI: 10.19082/5712
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between health literacy and health-related quality of life in patients with hypertension, in Tehran, Iran, 2015-2016

Abstract: Background and ObjectiveHypertension is considered an important public health problem in developed and developing countries. This disease is closely associated with the quality of life of patients, and it seems that health literacy plays a role in this regard. Due to lack of information on the role of health literacy on the quality of life in patients with hypertension, this study has aimed to determine the correlation between health literacy and health-related quality of life in patients with hypertension.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…To check whether the association between health literacy and quality of life and subjective health status is similar to what has been found in other studies (e.g., [33][34][35][36]), we first computed bivariate correlations between the respective variables and, in a second step, partial correlations with which we eliminated the influence of the control variables age, gender, and duration of school education. The results to our second research question can be summarized thus: the moderate bivariate correlation (r = 0.35) between health literacy and quality of life found by Zheng et al [10] in their meta-analysis could largely be confirmed in our sample: between health literacy and the two health outcomes (health-related quality of life and subjective health status), bivariate correlations of 0.41 (EQ-5D index) and 0.40 (EQ-VAS) resulted.…”
Section: Discussionmentioning
confidence: 79%
“…To check whether the association between health literacy and quality of life and subjective health status is similar to what has been found in other studies (e.g., [33][34][35][36]), we first computed bivariate correlations between the respective variables and, in a second step, partial correlations with which we eliminated the influence of the control variables age, gender, and duration of school education. The results to our second research question can be summarized thus: the moderate bivariate correlation (r = 0.35) between health literacy and quality of life found by Zheng et al [10] in their meta-analysis could largely be confirmed in our sample: between health literacy and the two health outcomes (health-related quality of life and subjective health status), bivariate correlations of 0.41 (EQ-5D index) and 0.40 (EQ-VAS) resulted.…”
Section: Discussionmentioning
confidence: 79%
“…Based on their titles and abstracts, 3274 articles met our criteria. After careful review, 23 studies [ 11 13 , 16 20 , 29 – 43 ] fulfilled our selection criteria for meta-analysis. The flow chart of this selection procedure is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“… Yanji, China 331 Hypertensive elderly (over 60 years, 63.4% female) Self-developed questionnaire containing Global QOL, Psychological general well-being, Symptom bother Self-developed questionnaire measuring health literacy about hypertension 9 Wenning D, et al 2015 [ 41 ] Cross-sectional November–December, 2014. Kunming, China 500 college students (age: 17–24 years, 56.7% female) Self-developed questionnaire measuring QOL of college students Self-developed questionnaire measuring health literacy of college students 8 Couture EM, et al 2017 [ 34 ] Cross-sectional Quebec, Canada 247 chronic Participants (age: 18–85 years, 55.5% female) SF-12v2 NVS 7 Halverson JL, et al 2015 [ 35 ] Cross-sectional 2006s-sect Wisconsin, America 1841 Wisconsin residents, newly diagnosed with lung, prostate, breast, or colorectal cancer(age: over 18 years, 50.8% female) FACT-G Self-developed questionnaire containing four questions validated in STOFHLA and REALM 8 Naimi AJ, et al 2017 [ 11 ] Cross-sectional Tehran, Iran 400 hypertensive patients (age: 18–89 years, 45.0% female) SF-36 HELIA 6 Song S, et al 2017 [ 38 ] Cross-sectional October ectionale patie South Korea 305 non-institutionalized adults (age: 20–60 years, 50.5% female) SF-36 REALM 6 Wang C, et al 2015 [ 31 ] Cross-sectional Northwestern China 913 poor rural women (age: 23–57) EQ-5D R-CAHLQ 6 Wang C, et al 2017 [ 13 ] Cross-sectional 2001s-sec Six towns,China 882 hypertensive patients (age: over 35 years, 56.1% female) SF-36 …”
Section: Resultsmentioning
confidence: 99%
“…One study conducted in rural western China found that enhancing the level of health literacy and raising self-management might improve the HRQoL of patients with hypertension [59] . Another study conducted in Tehran, Iran, concluded that health literacy and HRQoL had a signi cantly positive correlation and suggested that nursing o cials and policymakers take measures to promote patients' HRQoL by improving patients' health literacy levels [60] . Thus, it seems essential to improve the level of HBP-HL among Kazakh hypertension patients.…”
Section: Discussionmentioning
confidence: 99%